PHILOSOPHY OF THE TEXT “THE LEGEND OF BUKIT FAFINESU” FUNCTIONAL SYSTEMIC LINGUISTICS - Oktavianus Kaka; I Putu Eka Suardana; Ni Nyoman Ayu Tri Hidayanti (Focus Journal : Language Review, 2025)
The text "Legend of Fafinesu Hill" is a narrative text originating from the Province of East Nusa Tenggara. This text contains conditions of meaning that are still held by the local community. This study aims to explore the noble values conveyed in the text throughcomplex clauses. The theory used to dissect the noble values of this text is the theory of complex clauses from the theory of Systemic Functional Linguistics. This study uses a qualitative approach, grounded theory. The data sources taken from the text, namelysentences categorized as complex clauses. The results of this study indicate that this text teaches us to be grateful to God. In addition to into, this text teaches us to make sacrifices sincerely. This research is an applied language research so that the results of this study areuseful for education, discourse studies, semiotics, and sociolinguistics